2012
DOI: 10.1002/jbm.a.34158
|View full text |Cite
|
Sign up to set email alerts
|

Self‐supporting nanoporous alumina membranes as substrates for hepatic cell cultures

Abstract: Membranes made from nanoporous alumina exhibit interesting properties for their use in biomedical research. They show high porosity and the pore diameters can be easily adjusted in a reproducible manner. Nanoporous alumina membranes are thus ideal substrates for the cultivation of polar cells (e.g., hepatocytes) or the establishment of indirect co-cultures. The porous nature of the material allows supply of nutrients to both sides of adherent cells and the exchange of molecules across the membrane. However, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Cell proliferation increased with an increase in pore diameter and was highest on substrates with 200 nm pores. In contrast, cell functionality was fostered on membranes with small pore diameters of around 50 nm [21]. These results agree with the results obtained using 50-150 nm PAA and NIH-3T3 fibroblast cells [22], 20-200 nm pore size alumina and human osteoblast-like MG63 cells [23], and 75-300 nm pore size alumina and NIH 3T3 cells [24].…”
Section: Cell Growthsupporting
confidence: 90%
“…Cell proliferation increased with an increase in pore diameter and was highest on substrates with 200 nm pores. In contrast, cell functionality was fostered on membranes with small pore diameters of around 50 nm [21]. These results agree with the results obtained using 50-150 nm PAA and NIH-3T3 fibroblast cells [22], 20-200 nm pore size alumina and human osteoblast-like MG63 cells [23], and 75-300 nm pore size alumina and NIH 3T3 cells [24].…”
Section: Cell Growthsupporting
confidence: 90%
“…The ZnO-coated membranes examined in this study were previously shown to possess antibacterial activity; 16 however, the cytotoxicity of these materials was not previously examined. It is evident from the MTT cell viability assay results that the ZnO-coated membranes are cytotoxic to macrophages after 48 h of incubation.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have indicated that the pore size of nanoporous anodized aluminum oxide membranes and coated membranes does not have a significant effect on cell viability 24 . As noted in the introduction, our group quantified Zn ion release from 20 nm and 100 nm anodized aluminum oxide membranes with atomic layer-deposition grown 8 nm-thick ZnO coatings into DMEM culture media containing 10% fetal bovine serum by means of inductively coupled plasma mass spectrometry 16 . This study confirms that varying the pore size between 20 and 200 nm does not alter cell viability as measured by the MTT assay.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations